The cardioprotective effect of S. africana caerulea/Blue Sage in ischaemia and reperfusion induced oxidative stress - Salie, Ruduwaan; Lopes, John; Kotze, Leon; van Aarde, Ruzayda (Frontiers in Pharmacology, 2023)
Background: Since antiquity, alternative herbal remedies, such as S. africana caerulea/Blue Sage (BLS) water infusion extract (WIE) has been used by traditional healers, for the effective treatment of various chronic inflammatory disorders associated with reduced cellular antioxidant defense mechanisms and free radical cellular damage. In the heart, ischaemia—reperfusion (I/R) induced oxidative stress becomes an early crucial event in the pathogenesis of ischaemia—reperfusion injury (I/RI) and subsequent heart failure. Purpose/Aim: To investigate whether BLS WIE treatment during ischaemia and/or reperfusion may be cardioprotective. Study design: Isolated perfused rat hearts were exposed to 35 min regional ischaemia (RI) and 60 min reperfusion. The BLS WIE was applied: i) for the last 10 min of RI (PerT) or ii) from onset of reperfusion (PostT) or iii) both (PerT) + (PostT). Methods: Endpoints were functional recovery and infarct size (IS). In another set of experiments, left ventricles were freeze-clamped after RI and 10 min reperfusion for detection of total and phosphorylated p-ERK p44/p42, p-Akt, p-p38-MAPK, p-JNK, Nrf-2, NF-kB, Bax, Bcl-2, Caspase-3, and PGC-1α by Western blot analysis. Results: BLS (PostT) significantly increased ERK p44, p-Akt, Nrf-2, and Bcl-2 levels; significantly decreased p-p38-MAPK as well as p-JNK p46 phosphorylation; did not affect Bax levels and significantly decreased Bax/Bcl-2 ratios. This was associated with significantly reduced Caspase-3 levels and increased PGC-1α phosphorylation, particlarly when BLS WIE was administered as PostT. Conclusion: The administration of polyphenol-rich BLS WIE at different stages of ischaemia and/or reperfusion, activate/inhibit several signaling events simultaneously and mediate cardioprotection in a multitarget manner.